The influence of biological relatedness on sexual dimorphism and sex classification based on external morphology of the frontal bone - Hamanová Čechová, Markéta; Cvrček, Jan; Dupej, Ján; Brůžek, Jaroslav; Velemínská, Jana (International journal of legal medicine, 2024)
The most significant sexual differences in the human skull are located in the upper third of the face (the frontal bone), which is a useful research object, mainly in combination with virtual anthropology methods. However, the influence of biological relatedness on sexual dimorphism and frontal bone variability remains unknown. This study was directed at sexual difference description and sex classification using the form and shape of the external surface of the frontal bones from a genealogically documented Central European osteological sample (nineteenth to twentieth centuries). The study sample consisted of 47 cranial CT images of the adult members of several branches of one family group over 4 generations. Three-dimensional virtual models of the frontal bones were analyzed using geometric morphometrics and multidimensional statistics. Almost the entire external frontal surface was significantly different between males and females, especially in form. Significant differences were also found between this related sample and an unrelated one. Sex estimation of the biologically related individuals was performed using the classification models developed on a sample of unrelated individuals from the recent Czech population (Čechová et al. in Int J Legal Med 133: 1285 1294, 2019), with a result of 74.46% and 63.83% in form and shape, respectively. Failure of this classifier was caused by the existence of typical traits found in the biologically related sample different from the usual manifestation of sexual dimorphism. This can be explained as due to the increased degree of similarity and the reduction of variability in biologically related individuals. The results show the importance of testing previously published methods on genealogical data.
Keywords: Geometric morphometrics; Tomography, X-Ray Computed; Forensic anthropology; mužské pohlaví; Forensic Anthropology; Frontal Bone; Adult; Sex Determination by Skeleton; Genealogical documented sample; určení pohlaví podle kostry; ženské pohlaví; Humans; Sex Characteristics; zobrazování trojrozměrné; čelní kost; soudní antropologie; Imaging, Three-Dimensional; dospělí; Kinship; počítačová rentgenová tomografie; pohlavní dimorfismus; Female; lidé; Male